Opportunities and Challenges: Revitalising the Accounting Profession Against Artificial Intelligent - Yassin, Muhammad; Frihatni, Andi Ayu; Muhammadun, Muzdalifah (Riwayat: Educational Journal of History and Humanities, 2025)
Technological developments noting Artificial Intelligence have impacted many aspects of activities and sectors of society, including the accounting profession. Therefore, this research is intended to analyse the opportunities and challenges that the AI revolution has on the accounting profession, as well as formulate a strategy to revitalise the role of accountants in the digital era. In this research, a qualitative approach method was used through literature review techniques. Based on the research results, it was found that AI offers enormous opportunities in improving efficiency, accuracy, and productivity through the automation of routine tasks such as transaction recording, data analysis, and so on. However, a significant source of risk has also emerged at the same time, and is a concern for the accounting profession today and in the future. Harnessing Artificial Intelligence impacts the liquidation process and the generation of new jobs, requiring the accounting profession to continuously evolve through challenges that demand increased technical, strategic competence and a deep understanding of technology. accounting as a strategic partner in business decision making. This article recommends collaborative efforts between educational institutions, professional organisations, and companies. As well as the development of accounting professional resources that are aligned with current conditions, to prepare accountants for the changes brought by Aritficial Intelligence. With the right approach, Artificial Intelligence will not only be a challenge, but also an opportunity to strengthen the relevance and sustainability of the accounting profession in the future.